New species and sorts of perennial cereal grasses in the Middle Urals for hay and pasture use - Bezgodov A. V., Belyaev A. V., Ponomarev A. B. (Innovative technologis in science and education, 2016)
as a result of many years of breeding in the Ural Agricultural Research Institute 19 sorts of perennial grasses for mowing and pasture use , landscaping and land reclamation were created. This article summarizes the main reasons for the low yield of perennial grasses occupying in the region more than 300 thousand hectares or more than 70% in the structure of fodder crops planting. The authors give the characteristic of some new varieties, as well as provide refined elements of seeds cultivation technology of.
Keywords: сорт; пастбище; семенная продуктивность; sort; злаковые травы; укос; сенокос; продуктивное долголетие; pasture; seed production; cereal grasses; mowing; haymaking; productive longevity